2008
DOI: 10.1007/s11665-008-9225-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Yield Strength and Tensile Strength with Hardness for Steels

Abstract: Hardness values as well as yield and tensile strength values were compiled for over 150 nonaustenitic, hypoeutectoid steels having a wide range of compositions and a variety of microstructures. The microstructures include ferrite, pearlite, martensite, bainite, and complex multiphase structures. The yield strength of the steels ranged from approximately 300 MPa to over 1700 MPa. Tensile strength varied over the range of 450-2350 MPa. Regression analysis was used to determine the correlation of the yield streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
196
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(248 citation statements)
references
References 8 publications
12
196
0
8
Order By: Relevance
“…The two stress variables σ y and σ u are widely known to be highly positively correlated in steels [20,23,54,56,57] and data on them is widely available. It is desirable to regress h and n on σ u to generate a useful predictor relationship between these rarely measured variables (h and n) and a widely measured one (σ u ).…”
Section: Additional Regression Analyses On S235jr Grade Steelsmentioning
confidence: 99%
“…The two stress variables σ y and σ u are widely known to be highly positively correlated in steels [20,23,54,56,57] and data on them is widely available. It is desirable to regress h and n on σ u to generate a useful predictor relationship between these rarely measured variables (h and n) and a widely measured one (σ u ).…”
Section: Additional Regression Analyses On S235jr Grade Steelsmentioning
confidence: 99%
“…Other studies have shown that a narrow area with high hardness does not generally lead to toughness problems (see [22]). However, high hardness in the FZ causes a high mismatch ratio between base metal and FZ [28]. As our findings show, this overmatching is essential for FPD; for as welded specimens FPD was often observed, whereas in PWHT conditions, nearly no FPD occurred.…”
Section: Discussionmentioning
confidence: 52%
“…The HB values are then converted to σu by using Equation 3 as follows (Gaško, 2011;E.J. Pavlina, 2008), Other components such as shafts, bolts, and keys are excluded from the Figure. It can be seen that regardless of the meshing element size, the model exhibited a relatively lowstress value of between 0 and 150 MPa in most parts of its body.…”
Section: Hb Was Calculated By Equation 2 Asmentioning
confidence: 99%